1976
DOI: 10.1029/ja081i010p01751
|View full text |Cite
|
Sign up to set email alerts
|

Pc 4 and Pc 5 pulsations during storm recovery

Abstract: A strong pulsation event was observed in the magnetosphere near L = 5 with the flux gate magnetometer on Explorer 45. The event occurred near 2300 UT on June 18, 1972, during the recovery phase of a large magnetic storm. Explorer 45 was in the afternoon quadrant, and the event was also observed at many day side, ground level observatories at high and low latitudes. The event had a complex spectrum with distinct pulsations near 2, 6, and 14 mHz (500‐, 160‐, and 70‐s periods). The two lower‐frequency pulsations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1978
1978
1985
1985

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Walker et al [1982] showed that the curvature drift of the particles can also be effective in coupling the mirror instability to a shear Alfv•n wave. Storm time Pc 5 pulsations observed by satellites have been reported by various authors [Barefield and McPherron, 1978;Kokubun et al, 1977;Lanzerotti et al, 1975;Lin and Cahill, 1976;Suet al, 1977;Kremser et al, 1981]. Kremser et al [1981] have studied Pc 5 pulsations during a storm period using the particle flux data of GEOS 2 associated with the drift mirror instability of the compressional mode (i.e., essentially radial velocity fluctuation).…”
Section: Copyright 1985 By the American Geophysical Unionmentioning
confidence: 83%
See 1 more Smart Citation
“…Walker et al [1982] showed that the curvature drift of the particles can also be effective in coupling the mirror instability to a shear Alfv•n wave. Storm time Pc 5 pulsations observed by satellites have been reported by various authors [Barefield and McPherron, 1978;Kokubun et al, 1977;Lanzerotti et al, 1975;Lin and Cahill, 1976;Suet al, 1977;Kremser et al, 1981]. Kremser et al [1981] have studied Pc 5 pulsations during a storm period using the particle flux data of GEOS 2 associated with the drift mirror instability of the compressional mode (i.e., essentially radial velocity fluctuation).…”
Section: Copyright 1985 By the American Geophysical Unionmentioning
confidence: 83%
“…Kremser et al [1981] have studied Pc 5 pulsations during a storm period using the particle flux data of GEOS 2 associated with the drift mirror instability of the compressional mode (i.e., essentially radial velocity fluctuation). Lin and Cahill [1976] have explained Pc 5 pulsations observed by the Explorer [Radoski, 1972;Cummings et al, 1969;Singer et al, 1982]. Charged particle behavior in low-frequency geomagnetic micropulsations and particle flux modulation characteristics [Kokubun et al, 1977;Hughes et al, 1979;Lin and Parks, 1982] have provided additional information regarding the fundamental and harmonic mode oscillations which are of importance for understanding the nature of the source exciting the pulsation.…”
Section: Copyright 1985 By the American Geophysical Unionmentioning
confidence: 99%
“…The drift mirror and drift compressional instabilities have been examined as possible mechanisms in one wave event that was observed with Explorer 45 [Cahill, 1973] by Lanzerotti and Hasegawa [1975]. Observations by several researchers McPherron, 1972, 1978;Lin and Cahill, 1976] We will not take into account the spatial variations of the magnetic field, since the very long scale length involved only affects the equilibrium velocity space distribution of the hot particles. The stability of the plasma (to perturbations with frequencies at or above the diamagnetic drift frequency) is not affected by such field gradients.…”
Section: Introductionmentioning
confidence: 99%
“…This is because contributions from VB drift terms (a finite-fl effect) were either ignored [Lin and Parks, 1978;Patel and Migliuolo, 1980;Migliuolo and Patel, 1980] [1981a, b]). This renders the predictions of these models barely applicable to storm time Pc 4-5 pulsations, since storm time plasmas often have fl > 0.5 [Frank, 1967;Lanzerotti et al, 1974Lanzerotti et al, , 1975Hoffman et al, 1975;Lin and Cahill, 1976]. It is the intention of the present work to examine high-fl effects on low-frequency (compared to the ion cyclotron frequency) modes, in a self-consistent fashion.…”
mentioning
confidence: 99%